Self-Esteem Anak Sekolah Dasar dengan Disleksia - Arina Isyalhana; Farida Kurniawati (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2020)
Dyslexia is the most common specific learning disorder. Around 5% - 15% of elementary school students have dyslexia (APA,2013). Children with dyslexia might appear different at school and tend to get lower academic scores in comparison with theirpeers. Hence, this may increase the possibility for the children with dyslexia to have low self-esteem (Mash & Wolfe, 2016)because their peers’ opinions about them play an important role in affecting their self-esteem (Veenstra et al., 2007, dalamTaylor, Hume, & Welsh, 2010). The aim of this study is to give a representation about the effect of dyslexia to the self-esteemof elementary school students with the expectance to increase the awareness to detect and give early intervention to dyslexicchildren. The research method is literature review using articles obtained online from several databases. There were 5 selectedresearch articles with the criteria of the participants in the study aged between 6 – 12 years old, and the used the instrumentsto measure specific learning disorder and also self-esteem. The result of this literature review shows that dyslexia can affectthe self-esteem of elementary school students.